Important aspects of T‐cell collection by apheresis for manufacturing chimeric antigen receptor T cells. Issue 1 (13th October 2019) - Paroder, Monika; Le, Nguyet; Pham, Huy P.; Thibodeaux, Suzanne R.
Abstract: Chimeric antigen receptor (CAR)‐T cells have proven to be an effective cancer therapy for CD19‐expressing neoplasms. Efforts to optimize the manufacturing process can help to ensure the efficacy and safety of the therapy. Peripheral blood T cells, which serve as the source material, are collected by apheresis. However, the majority of apheresis collection protocols do not selectively collect T cells, but rather isolate the mononuclear cell (MNC) layer, which also contains other mononuclear leukocytes present in the peripheral blood. Since currently CAR‐T cells are autologous, the patient's clinical condition is a major factor in the planning, coordination, and execution of the apheresis procedure to subsequently manufacture the product successfully. Efforts have been made to identify predictors of a successful collection (ie, precollection peripheral blood CD3+ count). The characteristics of the source material influences the manufacturing process directly, and therefore affects the quantity, viability, immune cell composition, and T cell phenotypic makeup of the final product. Here we review the CAR‐T cell manufacturing process from the apheresis perspective, highlighting considerations before, during, and after collection that could potentially alter the outcome of the manufacturing process and ultimately, the safety and efficacy of the therapy for the patient.